2004
DOI: 10.1111/j.1432-1033.2004.04105.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of Helicobacter pylori arginase, RocF: unique features among the arginase superfamily

Abstract: The urea cycle enzyme arginase (EC 3.5.3.1) hydrolyzes l‐arginine to l‐ornithine and urea. Mammalian arginases require manganese, have a highly alkaline pH optimum and are resistant to reducing agents. The gastric human pathogen, Helicobacter pylori, also has a complete urea cycle and contains the rocF gene encoding arginase (RocF), which is involved in the pathogenesis of H. pylori infection. Its arginase is specifically involved in acid resistance and inhibits host nitric oxide production. The rocF gene was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
79
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 42 publications
10
79
0
Order By: Relevance
“…The ratio of the k cat /K 0.5 can provide an estimate of the apparent catalytic efficiency. The ratio for the Co 21 -enzyme is approximately fourfold higher than the Mn 21 -enzyme, which is consistent with the earlier report (11). This clearly suggests that the rate of reaction in the H. pylori enzyme depends on the nature of the divalent metal ions.…”
Section: Cooperativity and Concentration-dependent Oligomerization Ansupporting
confidence: 81%
See 3 more Smart Citations
“…The ratio of the k cat /K 0.5 can provide an estimate of the apparent catalytic efficiency. The ratio for the Co 21 -enzyme is approximately fourfold higher than the Mn 21 -enzyme, which is consistent with the earlier report (11). This clearly suggests that the rate of reaction in the H. pylori enzyme depends on the nature of the divalent metal ions.…”
Section: Cooperativity and Concentration-dependent Oligomerization Ansupporting
confidence: 81%
“…For holo proteins, the experiments were carried out after heat activation. The heat activation is reported to be essential for full activation of the arginases including H. pylori enzyme (10,11) and it has been suggested that one of the metal ions can go deep into the active site and form a bimetallic cluster. The heat-activated metal reconstituted protein showed approximately twofold higher activity than without heat activated (data not shown), consistent with other arginases that a bimetallic cluster is essential for full activation of the enzyme.…”
Section: Metal Ions Have Role In Tertiary Structure Of the Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…1D). In addition, XXT2 was eluted from the Ni-NTA column using a buffer containing imidazole, which has been shown to affect the activity of other enzymes (Cotovio et al, 1996;McGee et al, 2004;Zhang et al, 2011). To investigate the effect of imidazole on XXT2, activity assays were carried out in the presence of 250 mM imidazole and without imidazole in the reaction mixture.…”
Section: Optimization Of Activity Assay Conditionsmentioning
confidence: 99%